2018
DOI: 10.1002/psp.2165
|View full text |Cite
|
Sign up to set email alerts
|

Transnational families: Cross‐country comparative perspectives

Abstract: This special issue aims to address the gap in transnational families studies by identifying if there are common patterns and effects of transnational family life across countries and regions, using cross-country comparative analyses. In this editorial introduction, we highlight the overarching themes emerging from seven papers, which employ new large-scale surveys specifically designed to collect information about transnational family life across different Latin American, African, and Southeast Asian countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Conducting a comparative study across different contexts presents a number of challenges (Mazzucato & Dito, ). One critical challenge is operationalizing the conceptual domains across unique data sets to allow cross‐country comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Conducting a comparative study across different contexts presents a number of challenges (Mazzucato & Dito, ). One critical challenge is operationalizing the conceptual domains across unique data sets to allow cross‐country comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Literature on gender and migration has shown that women and men have different social network characteristics leading to different propensities to migrate, may have different reasons for migrating, and face different conditions overseas (Constable, ; Curran & Rivero‐Fuentes, ; Eremenko & González‐Ferrer, ; Liu, Riosmena, & Creighton, ; Malmusi et al, ; Toma & Vause, ). Yet there has been no systematic comparison of transnational families and in particular of migrant mothers and fathers (Mazzucato & Dito, ). This literature review summarises findings from different studies investigating the characteristics of female and male migrants and studies on transnational families that took the sex of the migrant parent into account, to inform our analyses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only recently have studies focussed on fathers (Poeze & Mazzucato, ; Pribilsky, ; Waters, ), indicating that fathers also suffer from the separation from their children, albeit in different ways. Finally, these studies are small‐scale and thus focus on transnational parents only (Mazzucato & Dito, ). They therefore cannot compare their findings with nontransnational parents, in order to identify what may be particular to being in a transnational family versus more general characteristics of a population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Temporalities of Migration and Family: Rhythms, Ruptures, and Reversals Mazzucato and Schans (2011) were among the first scholars to argue that "methodologically and theoretically, families are still predominantly conceived of as nuclear, living together, and bounded by the nation state. … Transnational families … have been treated as a temporary phenomenon, with family reunification in the host society the preferred outcome for all family members" (704; see also Mazzucato and Dito 2018). With the increasing ubiquity of the "permanently temporary" migrant in regimes of unflexible noncitizenship in Asia, attention to family morphologies that bear the marks of the seemingly transgressive forces of increased migrations and mobilities has become more urgent.…”
mentioning
confidence: 99%